2011
DOI: 10.1016/j.acvd.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Surgery and invasive procedures in patients on long-term treatment with direct oral anticoagulants: Thrombin or factor-Xa inhibitors. Recommendations of the Working Group on perioperative haemostasis and the French Study Group on thrombosis and haemostasis

Abstract: Direct oral anticoagulants (DOAs)--inhibitors of thrombin or factor-Xa--are expected to replace vitamin K antagonists in most of their indications. Patients receiving long-term treatment with DOAs are likely to be exposed to elective or emergency surgery or invasive procedures. Owing to the present lack of experience in such conditions, we cannot make recommendations, but only propose perioperative management for optimal safety regarding the risk of bleeding and thrombosis. DOAs may increase surgical bleeding,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(81 citation statements)
references
References 26 publications
0
79
0
2
Order By: Relevance
“…Italian experts have recently suggested that patients with previous deep hemispheric the last dose of rivaroxaban administered once daily. 29 The other approach has suggested that the first dose of LMWH should be given 24 h after the last dose of the TSOAC to limit the risk of bleeding and one might recommend this option in particular in subjects with lower CrCl values who were taking dabigatran. It is advisable to administer the last therapeutic dose of LMWH 24 h before surgery, and this should be half dose if was given once daily, like during bridging therapy in patients on VKAs.…”
mentioning
confidence: 99%
“…Italian experts have recently suggested that patients with previous deep hemispheric the last dose of rivaroxaban administered once daily. 29 The other approach has suggested that the first dose of LMWH should be given 24 h after the last dose of the TSOAC to limit the risk of bleeding and one might recommend this option in particular in subjects with lower CrCl values who were taking dabigatran. It is advisable to administer the last therapeutic dose of LMWH 24 h before surgery, and this should be half dose if was given once daily, like during bridging therapy in patients on VKAs.…”
mentioning
confidence: 99%
“…En dehors du champ strict de la chirurgie orale, des propositions et des suggestions ont été émises par le Groupe d'intérêt en hémostase périopératoire (GIHP) et le GEHT [259,260]. Dans le cadre de la chirurgie programmée, la poursuite du traitement par AOD est la règle en instaurant une fenêtre théra-peutique.…”
Section: Arrêt Ou Maintien Du Traitement Par Anticoagulant Oral Direct ?unclassified
“…Dans tous les autres cas, un relais en postopératoire par héparine est en général non nécessaire. Les AOD ayant un délai d'action très rapide, il ne doit y avoir aucun chevauchement avec le traitement par l'héparine [259,260] À la vue des profils d'efficacité et de sécurité des AOD dans les essais de phase III par rapport aux anticoagulants Devant l'insuffisance des données de la littérature, le groupe de travail a élaboré les recommandations concernant la gestion des AOD en chirurgie orale à partir d'une position dégradée de celle des AVK. Une bonne prise en charge des patients sous AOD en vue d'une intervention chirurgicale ou d'un acte invasif repose principalement sur des critères pharmacologiques tels le nombre de prise par jour, la demi-vie du produit, l'heure de la dernière prise, le délai et la dose de la première dose administrée après la chirurgie [16,259,260].…”
Section: Arrêt Ou Maintien Du Traitement Par Anticoagulant Oral Direct ?unclassified
See 1 more Smart Citation
“…Specifi c assays for the measurement of NOAC plasma concentrations are available in specialized laboratories and should be ordered in case of hemorrhagic events or emergent surgeries (Sié et al 2011 ;Pernod et al 2013 ).…”
Section: Novel Direct Oral Anticoagulants (Noacs)mentioning
confidence: 99%